(untitled) (Journal of Asian Development Studies, 2025)
Digital discourse and self-representation in social media can be understood as the means by which people create, express, and negotiate their identities through online linguistic, visual, and multimodal practices, especially on English-dominant platforms that reach global audiences. The study is based on three major research questions: how people form identities through linguistic and discursive means, how features of a platform and cultural requirements shape identity articulation, and how communication patterns and multimodal practices, dominated by English, shape social affiliation and self-perception. The study is designed using a qualitative research method that is premised on the analysis of documents and the qualitative interpretation of their content, as well as the examination of how people form identities through the application of linguistic and discursive strategies. The results indicate that identity construction is a strategic, performative, and adaptive act in which English is used as a pragmatic communication and symbolic resource for social placement, cultural affiliation, and visibility. Multimodal cues, including images, videos, emojis, hashtags, and stylized text, are used by users to create meaningful and authentic online personas as they navigate the negotiation of audience perception, algorithmic oversight, and platform conditions. Besides, the research shows that social validation through participation and conformity to community expectations is very important for validating online identity and belonging. Using Goffmanian dramaturgical approach, networked publics theory, and digital affordance theory, the study provides an overall perspective on digital identity as a socially mediated, technologically influenced phenomenon. The research adds to the theoretical basis and practical understanding and provides a guideline for scholars, educators, users, and platform developers interested in the convergence of language, technology, and identity within current English-dominant social media platforms.